Local Stories Adapted as Learning Tools Innovation of Fairy Tale for Teacher to Improve the Literacy Skills of Student in Secondary Schools - Umaya, Nazla Maharani; Suwandi, Sarwiji; Budiyono, Budiyono; Andayani, Andayani (International Journal of Pedagogy and Teacher Education, 2017)
One of the obstacles on the fairy tale of learning in secondary schools is there is not enough learning tool as an innovation. The example is found only one or two kind of teaching materials that use for learning, and only about 25% of the fairy tale text has from the local stories in each material. Student need more material than that to help them finish the study easily. The methods of research is exploratory mixed design. It's because the first sequent of this research is gathering qualitative data exploration for development, and collecting qualitative data to explain relationship found in the quantitative data (experimental result). An epic story is an object of the local stories chosen. All developed a tools consisting of a teacher guide, student books, and audiovisual. The result of this research is an increased literacy in students and the effectiveness of learning tools of the fairy tale for secondary school students. The conclusions is the study that the local story adapted as a learning tools innovation is effective to facilitate student learning and improve literacy skills better than regular tools. It can be a part of technical innovation competency development training of teachers in teaching.Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License